Realizing the benefits of cover crop legumes in smallholder crop-livestock systems of the hillsides of Central America : Trade-off analysis of using legumes for soil enhancing or as animal feed resource - Quintero, Marcela; Estrada, R.D.; Holmann, Federico J.; Rao, Idupulapati M.; Martens, S.; Peters, Michael; Hoek, Rein van der; Mena Urbina, Martin A.; Douxchamps, Sabine; Oberson, Astrid; Frossard, Emmanuel (International Center for Tropical Agriculture, 2009)
Presentation to the CGIAR Systemwide Livestock Programme Livestock Policy Group Meeting, 1 December 2009